One new species of free-living marine nematodes (Enoplida, Anticomidae, Cephalanticoma) from the Huanghai Sea - Huang, Y.; Zhang, Z. (Acta Oceanologica Sinica, 2007)
One new species of free-living marine nematodes Cephalanticoma filicaudata sp. nov. from the Huanghai Sea, China is described and illustrated. Cephalanticoma filicaudata sp. nov. is characterized by well developed cephalic capsule, three teeth at the anterior of oesophagus, excretory pore opens posterior to cervical setae, only two cervical setae per file, body length longer than 5 200?m, tail long and no ventral-lateral seta between the supplement and the cloacal opening. Types are deposited in the College of Marine Life Sciences, Ocean University of China.
NeMys doc_id: 17974